PROFITABILITY OF DIVIDEND PAYERS - Budiarso, Novi Swandari (Universitas Sam Ratulangi, 2017)
Most of the firms are looking for profits as their main objective which make them develops strategies to get the target profit. In circumstances that firms get the target profit, then normally they shall distribute the earnings as dividends to shareholders. The objective of this study is to provide an empirical finding about profitability between firms namely higher dividend payers and lower dividend payers. This study uses data of listed firms in period of 2010 to 2016 which drawn from Indonesia Stock Exchange. This study uses 146 listed firms in period of 2010 to 2016 which gives 1022 as total observe data. In term of hypothesis testing, this study uses mean difference test. This study finds that firms with higher dividends have better profitability rather than the lower which means this study accepts the hypothesis that higher dividend payers have better profitability.